IMPLEMENTATION OF LICENSING IN SOCIAL PROTECTION: Regional Achievements and Challenges - Bornarova, Suzana; Ilievski, Vladimir (Ревија за социјална политика/Journal of Social Policy, 2015)
A license is a document (work permit) issued by an official body(most commonly chamber) to persons – professionals, institutions,programmes, projects. It is an instrument used by the state to supervise theentire process of development of the social protection, in terms of:adequate quality of the institutions; adequate operation of the institutions;adequate services delivered to beneficiaries; professional qualificationsand development of professionals; continuing upgrading of the knowledgebase (Bornarova, 2004).